Implementasi Gaya Kepemimpinan Situasional Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru SD Negeri 006 Terpadu Kubang Jaya Kecamatan Siak Hulu Kabupaten Kampar - Isrok; M. Damrah Khair; Sri Lestari (Journal of Islamic Education and Learning, 2023)
The objectives of this study are to ascertain 1) The leadership style of the Principal of SD Negeri 006 Terpadu Kubang Jaya, and 2) How the Madrasa Head has implemented situational leadership to raise the professionalism of the teachers at SD Negeri 006 Terpadu Kubang Jaya. In this study, a qualitative approach is used to describe any research information that was gleaned from interviews, field observations, and documentation review. These methods are all aimed at elucidating the research's topic, and the data collected is then analyzed through data reduction, data presentation, and conclusion drawing. This aims to address the issue with the principal's managerial style. The outcomes demonstrated that the leadership of the SD Negeri 006 Terpadu Kubang Jaya principal included leadership positions as educators, managers, administrators, and leaders in the field of education. In order to increase the professionalism of the teachers at SD Negeri 006 Terpadu Kubang Jaya, the madrasa head's situational leadership style is being put into practice. Part of this process involves organizing and formulating each teacher's role, specifically by deciding on that role based on the results of a meeting decision to do so. Additionally, building connections with teachers involves allowing for open dialogue with them and giving them opportunity to employ their full ability in assisting with student learning.